Case report: Use of peripheral nerve stimulation for treatment of pain from vertebral plana fracture - Javed, Saba; Perry, Kenneth; Mach, Steven; Huh, Billy (Frontiers in Pain Research, 2023)
Vertebral plana fractures are a severe form of compression fractures that can cause significant morbidity due to incapacitating pain. Due to the flattening of the vertebrae in a plana fracture, accessing the vertebral body transpedicularly can be difficult, making traditional vertebral augmentation treatment dangerous. These injuries also typically occur in elderly patients with contraindications to invasive procedures. Peripheral nerve stimulation is a relatively new and minimally invasive treatment that uses electrical stimulation to inhibit pain signals from reaching the somatosensory cortex. Our case describes an 80 Year old female with multiple comorbidities and refractory pain due to a vertebral planar fracture successfully treated with a 60 day course of peripheral nerve stimulation as evidenced by over 50% reduction in symptoms and discontinuation of opioid pain medication use.